# How do you find the derivative of #y = (x+2)/(x-2) #?

By signing up, you agree to our Terms of Service and Privacy Policy

To find the derivative of ( y = \frac{x+2}{x-2} ), you can use the quotient rule, which states that if ( y = \frac{u}{v} ), then ( y' = \frac{u'v - uv'}{v^2} ), where ( u ) and ( v ) are functions of ( x ), and ( u' ) and ( v' ) represent their respective derivatives with respect to ( x ).

Let ( u = x + 2 ) and ( v = x - 2 ). Then ( u' = 1 ) and ( v' = 1 ).

Now apply the quotient rule: [ y' = \frac{(1)(x - 2) - (x + 2)(1)}{(x - 2)^2} ]

Simplify: [ y' = \frac{x - 2 - x - 2}{(x - 2)^2} ] [ y' = \frac{-4}{(x - 2)^2} ]

So, the derivative of ( y = \frac{x+2}{x-2} ) is ( y' = \frac{-4}{(x - 2)^2} ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the derivative of #1/(1 + x^4)^(1/2)#?
- How do you differentiate #f(x)=((65e^-7x)+2)^3 # using the chain rule?
- How do you use the chain rule to differentiate #y=1/(t^2+3x-1)#?
- How do you differentiate #f(x)=(1/x)*e^x*tanx-x*cosx# using the product rule?
- What is the derivative of #f(x)=(e^(2x))(ln(x))#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7